If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g + -14 = 46 Reorder the terms: -14 + g = 46 Solving -14 + g = 46 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + g = 46 + 14 Combine like terms: -14 + 14 = 0 0 + g = 46 + 14 g = 46 + 14 Combine like terms: 46 + 14 = 60 g = 60 Simplifying g = 60
| m+31=-33 | | p/-4=10 | | 2x^2-12x=864 | | p-1=14 | | 91=s+26 | | 3=h/4 | | h/2=-3 | | -1=t/2 | | 6(y-4)+2y=72-8y | | 2=z-5 | | ln(2x+1)+ln(x-7)=lnx+ln(2x-3) | | (72000-64800/7200)*100 | | 4(3)-5=7 | | 63-3u=4u | | -2+3y=y-2-4t | | 3x+2+x=x-5 | | 18-(-x)=3 | | 60=8x*1 | | 9+8m-5=6m+19-3m | | X+0.06X=35000 | | (12x(y^-6)(z^5))/11(x^-4)(y^8) | | 7X^2=2(X-9) | | 2n^2-4n=-42 | | 2n^2-4n=42 | | 0=(x+0.6)(x+0.6)(x-0.4)+0.148 | | 96=2(14+2b) | | 108=3*12x | | A=1/9xm^2s | | (x+1+4i)(x+1-4i)= | | 3x-4.2=1 | | 25x^2+(61x^2y^2)+36y^4= | | 11x-4=7x+6 |